1900 Miss. Laws 51-52 - (:unkn) unknown (My University, 1900)
Ch. 49: The auditor of the public accounts shall, by the first day of February in each year, furnish the clerk of the board of supervisors of each county with three copies of blank assessment rolls, and counties having two judicial districts shall be furnished with four copies; said roll shall be made of good paper, neatly and substantially bound and properly ruled and headed for the assessment of personal property and polls, in which to enter the following items: . . . sixteenth column, number of guns over one; seventeenth column, number of pistols, bowie knives, dirks or sword canes[.]
Keywords: REGISTRATION